AVALIAÇÃO DO ESPAÇO DISPONÍVEL PARA ERUPÇÃO DOS SEGUNDOS E TERCEIROS MOLARES SUPERIORES PERMANENTES APÓS A DISTALIZAÇÃO DOS PRIMEIROS MOLARES SUPERIORES PERMANENTES - Silva, Francisco Alexandre Baptista da (2008)
This study aimed to cephalometrically evaluate the space and positioning of crowns of unerupted permanent maxillary second and third molars at the region of the maxil-lary tuberosity during distalization of maxillary first molars, as well as to verify the cor-relation between these two variables. The sample was composed of 38 right lateral cephalograms, obtained of 19 young Brazilian patients, both Caucasoid and of Afri-can descent, being 6 males and 13 females, with mean age 9 years 5 months 13 days. The methodology initially comprised division of periods, namely initial (T1) and after distalization of the permanent maxillary first molar (T2) in a mean period of 10 months and 23 days. The space and angulation of existing crowns was analyzed with the aid of an intracranial reference line (line M), which was delineated from two points, the point SE located on the sphenoethmoidal suture, and the point Pt located at the anterior region of the pterygopalatine suture. This reference line was trans-ferred to the point F (line M ), located at the most posterior and inferior region of the maxillary tuberosity. The evaluated space was located from the line M to the distal aspect of the permanent maxillary first molar. Statistical analysis was performed by the Student s t test; correlation between the space and angulation was calculated by the Pearson correlation coefficient. It was concluded that the corresponding space between the distal aspect of permanent maxillary first molars and the end of the max-illary tuberosity, at the initial stage and after distalization, is not enough for the erup-tion of permanent maxillary second and third molars. The angulation of crowns in the initial period and after distalization revealed distal angulation of the crowns. With re-gard to the correlation of angulations of crowns of the permanent maxillary second and third molars and the space for eruption, it was observed that the greater the dis-tal angulation of crowns, the smaller will be the space available for eruption.(AU)